2023
DOI: 10.1007/s00246-023-03229-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Pulmonary Artery Stenting After Bidirectional Cavopulmonary Connection (BDCPC) in Single Ventricle Circulation

Abstract: After bidirectional cavopulmonary connection (BDCPC) central pulmonary arteries (PAs) of single ventricle (SV) patients can be affected by stenosis or even closure. Aim of this study is to compare SV patients with and without PA-stent implantation post-BDCPC regarding risk factors for stent implantation and outcome. Single center, retrospective (2006–2021) study of 136 SV consecutive patients with and without PA-stent implantation post-BDCPC. Patient characteristics, risk factors for PA-stent implantation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We have recently investigated the reasons for LPA stenosis and found that patients with a single right ventricle and history of a Norwood I surgery required more frequently LPA stenting, and that the diameter of the reconstructed ascending aorta after DKS anastomosis was an independent risk factor ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently investigated the reasons for LPA stenosis and found that patients with a single right ventricle and history of a Norwood I surgery required more frequently LPA stenting, and that the diameter of the reconstructed ascending aorta after DKS anastomosis was an independent risk factor ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis of the central pulmonary arteries is frequent and leads to an obstruction and imbalance of pulmonary blood flow (4,5). The left pulmonary artery (LPA) is mainly affected, as it may be compressed by the dilated (neo-)ascending aorta, or be hypoplastic due to a reduced blood flow (6)(7)(8). In these cases, the treatment of choice is percutaneous stent implantation, since it is minimally invasive, and the radial force of the stent permits to overcome external vessel compression (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our institution has extended the scope of interventions to include the LPA stenting in this patient group before rather than after the Fontan procedure. Also, in the second interstage period, pulmonary artery stent implantation emerges as a reliable and secure procedure, fostering harmonious growth of the pulmonary arteries [11].…”
Section: Balloon Angioplasty and Stent Implantationmentioning
confidence: 99%